2013
DOI: 10.1002/star.201200224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grain milling on starch structures and flour/starch properties

Abstract: Milling or grinding of cereal grains to produce flour is frequently accompanied by damage to starch granules, disruption of starch crystalline structure, and degradation of starch molecules. Amylopectin (AP) molecules are more susceptible to degradation than amylose (AM) molecules as AM molecules, present in amorphous conformation in native starch granules, are more flexible than the rigid double helical crystallites made of AP branches. The changes of starch structures caused by milling alter starch propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(105 citation statements)
references
References 57 publications
3
102
0
Order By: Relevance
“…While according to Song, Lee, Lee, and Yoon (2014), particle size is an important factor in biochemical reactions, as it significantly affects the physicochemical properties of flour by increasing the surface area per volume unit. The differences in damaged starch content and particle size distribution between flours would affect the pasting (Ashida, 2014) and thermal profiles, which have great influence on the quality of processed food products (Li, Dhital, & Hasjim, 2014) such as noodles (Hormdok & Noomhorm, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While according to Song, Lee, Lee, and Yoon (2014), particle size is an important factor in biochemical reactions, as it significantly affects the physicochemical properties of flour by increasing the surface area per volume unit. The differences in damaged starch content and particle size distribution between flours would affect the pasting (Ashida, 2014) and thermal profiles, which have great influence on the quality of processed food products (Li, Dhital, & Hasjim, 2014) such as noodles (Hormdok & Noomhorm, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that DS content of maize flours increased with increasing average particle size (employing the same sieve during milling). The milling operation affects directly the starch structure (Li et al 2014). It can be observed that the flours obtained with a sieve of 200 μm showed higher DS content than 500 μm flours due to higher mechanical and thermal damage caused during milling.…”
Section: Resultsmentioning
confidence: 99%
“…As TS was not dependent on milling SDRI was also higher in flours from mill 2. Li et al (2014) indicate that damaged starch granules in flour (level 6 structure) have greater enzyme digestibility than intact native starch granules and starch digestibility of flours from milled cereal grains increases with the decreasing flour size. Tef flours from mill 2 have the lower mean particle size and higher starch damage ( Table 2).…”
Section: Starch Fractions and In Vitro Starch Digestibilitymentioning
confidence: 99%